Exchange server 2010 portable command guide : MCTS 70-662 and MCITP 70-663 - Robb, Richard (Pearson IT Certification, 2011)
The compact, convenient Exchange Server 2010 command reference: every command MCTS 70-662 and MCITP 70-663 exam candidates need! Practical, example-rich, tip-filled information on every Exchange Server 2010 command required by Microsoft's MCTS 70-662 and MCITP 70-663 exams, plus other day-to-day Exchange Server commands Real-world scenarios that help professionals work and study more efficiently The perfect take-anywhere resource: no need to carry thick books or get on the Internet To maximize your effectiveness as an Exchange Server 2010 professional, you must keep track of hundreds of commands, keywords, command arguments, options, and prompts. Microsoft's MCTS 70-662 and MCITP 70-663 exams test you on many of those. Familiarizing yourself with all these commands is a daunting task. Exchange Server 2010 Portable Command Guide: MCITP 70-662 and 70-663 brings them all together in one compact, portable, easy-to-use reference. Packed with configuration examples, real-world scenarios, and expert usage tips, this book covers the key commands IT professionals need to know for Exchange Server 2010, from basic concepts to advanced techniques. It's the perfect take-anywhere guide to running Exchange Server 2010 environments - and for passing Microsoft's two key Exchange Server 2010 enterprise messaging exams.